A Nine-Year Audit of Open-Access Upper Gastrointestinal Endoscopic Procedures: Results and Experience of a Single Centre - Dean Keren; Tova Rainis; Edy Stermer; Alexandra Lavy (Canadian Journal of Gastroenterology)
BACKGROUND: The appropriateness and safety of open-access endoscopy are very important issues as its use continues to increase.